Efficacy of digital volume tomography in the preoperative assessment of position of inferior alveolar canal with impacted mandibular third molars in a subset of Indian population - Biyas Bhowmik; Venkatesh G Naikmasur; Kruthika Satyabodh Guttal (Wolters Kluwer Medknow Publications, 2018)
Context: Choosing an imaging source, which provides minimum radiation exposure to the patient, to facilitate surgical removal of impacted mandibular third molars (MTMs), thereby avoiding unwanted neurological complications. Aim: The aim of the study was to assess the efficacy of digital volume tomography (DVT) in evaluating the position of inferior alveolar canal (IAC) in relation to impacted MTMs and comparing it with conventional radiography (CR) in a subset of the Indian population. Materials and Methods: Four experienced observers assessed two groups: 33 DVT and 33 CR images, for the position of root-tips of impacted MTM in the proximity to IAC, in both vertical and horizontal planes. The diagnostic information was compared in both the groups. Statistical Analysis: Chi-square test, Mann-Whitney U-test, and Kappa statistics were used. Results: Comparison between DVT and CR revealed no statistically significant variation in assessing relationship in the vertical plane. There was, however, a significant difference between the groups, while comparing the diagnostic information for the horizontal dimension, for both the mesial and the distal roots, with an advantage for DVT (P < 0.05 for both mesial and distal roots). Conclusion: DVT is highly accurate in predicting neurovascular bundle exposure. It is indispensable for preoperative evaluation of impacted MTM.